All‐Printed Multilayers and Blends of Poly(dioxythiophene) Derivatives Patterned into Flexible Electrochromic Displays. Issue 2 (27th October 2022) - Brooke, Robert; Petsagkourakis, Ioannis; Majee, Subimal; Olsson, Oliver; Dahlin, Andreas; Andersson Ersman, Peter
Abstract: Low‐cost, flexible and thin display technology is becoming an interesting field of research as it can accompany the wide range of sensors being developed. Here, the synthesis of poly(dimethylpropylene‐dioxythiophene) (PProDOT‐Me2 ) by combining vapor phase polymerization and screen printing is presented. A multilayer architecture using poly(3, 4‐ethylenedioxythiophene) (PEDOT) and PProDOT‐Me2 to allow for electrochromic switching of PProDOT‐Me2, thereby eliminating the need for a supporting transparent conductive (metal oxide) layer is introduced. Furthermore, the technology is adapted to a blended architecture, which removes the additional processing steps and results in improved color contrast (∆ E * > 25). This blend architecture is extended to other conductive polymers, such as PEDOT and polypyrrole (PPy), to highlight the ability of the technique to adjust the color of all‐printed electrochromic displays. As a result, a green color is obtained when combining the blue and yellow states of PEDOT and PPy, respectively. This technology has the potential to pave the way for all‐printed multicolored electrochromic displays for further utilization in printed electronic systems in various Internet of Things applications. Abstract : Blends and multilayers of conducting polymers are developed and demonstrated in all‐printed electrochromic displays. The electrochromic layers are synthesized through a combination of vapor phase polymerization and screen printing. Displays with multiple colors and high color contrast are obtained by combining poly(dimethylpropylene‐dioxythiophene) (PProDOT‐Me2 ) or polypyrrole (PPy) with poly(3, 4‐ethylenedioxythiophene) (PEDOT), where the latter obviates the need of transparent conductive oxides.